2023
DOI: 10.1073/pnas.2218247120
|View full text |Cite
|
Sign up to set email alerts
|

Biolistic delivery of liposomes protected in metal-organic frameworks

Abstract: Needle-and-syringe-based delivery has been the commercial standard for vaccine administration to date. With worsening medical personnel availability, increasing biohazard waste production, and the possibility of cross-contamination, we explore the possibility of biolistic delivery as an alternate skin-based delivery route. Delicate formulations like liposomes are inherently unsuitable for this delivery model as they are fragile biomaterials incapable of withstanding shear stress and are exceedingly difficult t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Liposomes were synthesized and encapsulated in ZIF-8 using a previously published protocol (encapsulation with 20 mM zinc acetate and 640 mM 2-methylimidazole). 26 Cell culture, cytotoxicity measurement, and IC 50 determination A549, LLC-1, and OE33 cells were cultured in DMEM supplemented with FB essence, L-glutamine, and penicillinstreptomycin in T75 asks. All cells were grown at 37 °C, 5% CO 2 till 80% conuence.…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liposomes were synthesized and encapsulated in ZIF-8 using a previously published protocol (encapsulation with 20 mM zinc acetate and 640 mM 2-methylimidazole). 26 Cell culture, cytotoxicity measurement, and IC 50 determination A549, LLC-1, and OE33 cells were cultured in DMEM supplemented with FB essence, L-glutamine, and penicillinstreptomycin in T75 asks. All cells were grown at 37 °C, 5% CO 2 till 80% conuence.…”
Section: Instrumentsmentioning
confidence: 99%
“…12,13 ZIFs are unique as polymeric materials due to their kinetic lability; phosphate and carbonate salts, or albumin-rich environments readily pull the zinc from the framework causing it to dissolve completely, returning the original antigen to its pristine state. 14,15 ZIF's versatility in capturing, preserving, and releasing antigens is exceptional and has been used to encapsulate whole viruses, 16,17 bacteria, 18 proteins, 19,20 DNA, 21,22 RNA, 23 yeast, 24 liposomes, 25,26 enzymes, 27,28 glycans, 29 and carbohydrates. 30 We have recently shown that ZIF-encapsulated formulations exhibit a depot effect, which signicantly enhances the efficacy of vaccine models.…”
Section: Introductionmentioning
confidence: 99%
“…34,35 Finally, most immunotherapeutic drugs require multiple doses through needle and syringe, requiring technical skills that cannot be quickly transferred to the general population or volunteers. 36 Disposable needles result in biohazardous waste, and their accidental (or intentional) reuse spreads bloodborne pathogens worldwide. 37 While intramuscular injections are more straightforward than intravenous injections, they are prone to neurovascular injuries.…”
Section: Introduction To Vaccines and Immuno-therapeutics And Current...mentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) are crystalline materials formed through the coordination of organic linkers to metal nodes. 1 MOFs are used in a variety of applications such as biomedicine, 2–6 catalysis, 7,8 sensors, 9–11 conductors, 12–15 gas storage and separations. 16–20 The capture and storage of CO 2 is a growing area of research.…”
Section: Introductionmentioning
confidence: 99%